Dissociation dynamics of diatomic molecules in intense laser fields: a scheme for the selection of relevant adiabatic potential curves - Magrakvelidze, Maia; Aikens, Christine M.; Thumm, Uwe P. E. (My University, 2012)
We investigated the nuclear dynamics of diatomic molecular ions in intense laser fields by analyzing their fragment kinetic-energy release (KER) spectra as a function of the pump-probe delay τ . Within the Born-Oppenheimer (BO) approximation, we calculated ab initio adiabatic potential-energy curves and their electric dipole couplings, using the quantum chemistry code GAMESS. By comparing simulated KER spectra as a function of either τ or the vibrational quantum-beat frequency for the nuclear dynamics on both individual and dipole-coupled BO potential curves with measured spectra, we developed a scheme for identifying electronic states that are relevant for the dissociation dynamics. We applied this scheme to investigate the nuclear dynamics in O[subscript 2][superscript +] ions that are produced by ionization of neutral O[subscript 2] molecules in an ultrashort infrared (IR) pump pulse and dissociate due to the dipole coupling of molecular potential curves in a delayed IR probe laser field.
Keywords: Kinetic-energy release; Diatomic molecular ions; Intense laser fields